The Relationship between Alexithymia and Aggressive Behavior among Patients at Eradah and Mental Health Complex in Jeddah - Al-Hazazi, Muhmmad Yahya (Journal of Educational and Psychological Sciences, 2022)
The study aimed to investigate the relationship between alexithymia and aggressive behavior among the patients of Irada and mental health complex in Jeddah. To this aim, the study has employed the correlative descriptive approach. Members of the sample group were an randomly selected and were composed of (65) patients from the Irada and mental health complex in Jeddah, The study has employed a scale to measure the alexithymia(Tas-20), designed by (Bagby at el., 1994), translation (Al-Eidan, 2019), in addition to the aggressive behavior scale, designed by (Buss & Perry, 1992) and translated into Arabic and legalized it on the Saudi environment by (Abdullah & Abu Abaah, 1995). The results of the study showed the mean scores of the variables of alexithymia and aggressive behavior, the study also revealed the existence of a correlation between alexithymia and aggressive behavior, and the study recommended expanding the research that studies the level of Alexithymia, its relationship and its effect on many personality disorders due to the scarcity of its research and the preparation of counseling sessions for the guided.
Keywords: Alexithymia; Aggressive behavior; Addiction; Eradah and Mental Health Complex